Metode socialnega dela s starimi ljudmi in njihova uporaba pri delu z ljudmi z demenco - Ambrožič, Maja (Socialno delo, 2015)
Aging population requires new methods of work with older people, forcing us to discover new ways to cope with the challenges posed by aging and old age. The multidisciplinary integration of disciplines is very important because it contributes to the quality of aging and gives older people a voice. Working with the elderly is specific and, specifically in social work, encompasses an important space of research and interweaves theory with practice. In this context, it is necessary to rely on the concepts of social work, which direct the social worker towards personal work and throughout the working relationship. Methods of social work with the older people vary considerably. The method of personal planning is paramount and used increasingly in practice, its purpose being to preserve users' influence over important decisions in their life. The authors present methods of working with people with dementia and offer a broader insight into the methods of personal planning and advocacy. At the same time they depict the history of the development of social work with the elderly.
Keywords: agenig; staranje; education; izobraževanje; koncepti; concepts; strokovnjaki; experts; help; pomoč; history; zgodovina; social work; socialno delo